2013
DOI: 10.1115/1.4023748
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Mixed Convection in Vertical, Open-Ended, Concentric and Eccentric Annular Channels

Abstract: An Experimental Study of Mixed Convection in Vertical, Open-Ended, Concentric and Eccentric Annular ChannelsThe effect of eccentricity on heat transfer in upward flow in a vertical, open-ended, annuiar channel with a diameter ratio of 0.61, an aspect ratio of 18:1, and both internal surfaces heated uniformly has been investigated experimentally. Results have been reported for eccentricities ranging from the concentric case to the near-contact case and three inlet bulk Reynolds numbers, equal approximately to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Flow field was examined (forced to mixed convection) over the range of conditions: flow velocity = 0.13, 0.23, 0.27 m/s with Re = 53, 94, 118, respectively. Investigation by [7] reported that Strouhal number increased slowly with Ri. Flow and heat transfer characteristics were also explored experimentally.…”
Section: Previous Investigationsmentioning
confidence: 98%
“…Flow field was examined (forced to mixed convection) over the range of conditions: flow velocity = 0.13, 0.23, 0.27 m/s with Re = 53, 94, 118, respectively. Investigation by [7] reported that Strouhal number increased slowly with Ri. Flow and heat transfer characteristics were also explored experimentally.…”
Section: Previous Investigationsmentioning
confidence: 98%
“…1 In a reactor core, during the accident conditions, the passive decay heat removal system in the reactor becomes active, throughout the long-term cooling phase, circulation of the coolant in fuel assembly is driven by buoyancy, and a mixed convection regime may occur under such conditions with a low flow rate. 2 In the early studies of convection, heat transfer, natural convection, and forced convection were usually studied separately, while the interaction between them was ignored. Since mixed convection is a combination of forced convection and natural convection and may occur in many technological and industrial applications, with the development of science and technology, more and more experimental and theoretical studies on mixed convection have been carried out in open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed convection flows, which are also known as combined free and forced convection flows, occur in many technological and industrial applications and are driven by both external force and density difference 1 . In a reactor core, during the accident conditions, the passive decay heat removal system in the reactor becomes active, throughout the long‐term cooling phase, circulation of the coolant in fuel assembly is driven by buoyancy, and a mixed convection regime may occur under such conditions with a low flow rate 2 . In the early studies of convection, heat transfer, natural convection, and forced convection were usually studied separately, while the interaction between them was ignored.…”
Section: Introductionmentioning
confidence: 99%